A cast aluminum-copper alloy and a method of making the same
Patent Information
- Application Number
- CN202410035353.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-10
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-01-10
AI Technical Summary
[0006]上述专利中的铝铜合金随具有良好流动性,但是成分复杂,而且作为铝铜合金中的主要合金元素Cu含量较少,会使得铝铜合金中的主要强化相Al2Cu含量较少,从而导致合金整体力学性能较低
[0022]与现有技术相比,本发明的优点在于:在铝铜系铸造铝合金中,仅含有Cu、Mg、Mn、Ce及Al,无其他元素,保证了成分简单。其中,添加小于1wt.%的稀土Ce,使合金产生明显的晶粒细化,使得枝晶间距变窄;同时Ce的加入,还会使晶界处的Al2Cu和Al6Mn第二相形貌由连续网状转变为不连续骨架状,减轻了第二相对基体的割裂作用,改善了合金的室温力学性能。此外,Ce的加入,还会生成耐高温的硬质稀土化合物Al8Cu4Ce,对晶界产生“钉扎”效应,有效地阻碍了高温下晶界的滑移,提高了合金的高温力学性能。另外,本发明通过添加稀土Ce,吸收熔体中的氢,减少熔体中氧化夹杂,从而使熔体净化,从而增大合金的流动性。并且Ce的加入降低合金固相线温度和Al2Cu共晶温度,延长了熔体流动的时间,推迟枝晶相干,增加熔体大量进给的时间,提高了Al-Cu合金熔体流动性,使合金的充型能力得到提高。上述铸造铝铜合金满足汽车发动机缸体零件的制备要求,且满足大规模生产的需求。
Smart Images

Figure CN117737531B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aluminum-copper alloy casting technology, specifically relating to a casting aluminum-copper alloy and its preparation method. Background Technology
[0002] Aluminum-copper alloys possess excellent room-temperature and high-temperature mechanical properties, as well as machinability, and have been widely used in automotive components, especially engine block parts. Due to the requirements of engine structure and service performance, existing engine components are often designed with complex structures such as thin walls and pipes. However, aluminum-copper alloys have a wide solidification range, and the actual fluidity of the alloy during solidification is poor, making it difficult to compensate for shrinkage in the later stages of solidification and prone to phenomena such as incomplete casting, shrinkage porosity, and shrinkage cavities.
[0003] The fluidity of aluminum-copper alloys is influenced by many factors, primarily categorized into casting process factors and metallurgical factors. Casting process factors include the shape and dimensions of the casting, interfacial heat transfer coefficients, mold temperature, and mold material. Metallurgical factors include alloy composition, melt superheat, viscosity, and solidification mode. In the production of complex castings, the fluidity of the melt is typically improved by increasing its superheat. However, high melt superheat can lead to excessive grain growth in the casting, resulting in coarse grain structure and thus reducing the mechanical properties of the casting.
[0004] Therefore, another way to improve melt fluidity has emerged: adjusting the fluidity of aluminum alloys by changing the alloying elements. Compositional changes affect the alloy's viscosity, grain size, solidification range, and solidification mode, thus influencing its fluidity properties. For example, Chinese invention patent application CN201710618763.6 (publication number CN107385296A) discloses an aluminum-copper alloy material containing the following components by weight percentage: copper 1%–4%, titanium 2%–5%, iron 0.1%–1.5%, silicon 0.2%–1.5%, rare earth elements <1%, and the remainder being aluminum; the rare earth elements are at least one selected from lanthanum, cerium, neodymium, and yttrium; the preparation method includes the following steps:
[0005] (1) Casting; (2) Heat treatment. The aforementioned aluminum-copper alloy material has high strength, excellent plasticity, and good fluidity. After casting, it is not easy to have defects such as sand holes, porosity, and shrinkage.
[0006] While the aluminum-copper alloy in the aforementioned patent exhibits good fluidity, its complex composition and low content of Cu, the main alloying element, result in a low content of Al₂Cu, the primary strengthening phase, leading to overall lower mechanical properties. Furthermore, the extensive use of Ti as an alloying element increases the alloy's viscosity, hindering casting performance and failing to meet casting requirements.
[0007] Furthermore, while rare earth elements are widely used in aluminum alloys, their role in aluminum-copper alloys is relatively limited. Taking the rare earth element Sc as an example, although adding a certain amount of Sc increases the as-cast mechanical properties of the alloy, under the same aging heat treatment time, the mechanical properties of the alloy actually decrease. Moreover, the viscosity of the alloy also increases, thus reducing the overall casting performance of the alloy. In addition, although existing technologies disclose that rare earth elements in magnesium alloys can maintain good mechanical properties and fluidity, a relatively large amount of rare earth elements, approximately 1%, is required to maintain these properties. Due to the high price of rare earth elements, such a large addition would restrict large-scale industrial production. Summary of the Invention
[0008] The first technical problem to be solved by the present invention is to provide a method that, while ensuring the simplicity of the composition, achieves high fluidity, filling capacity and mechanical properties, in light of the current state of the prior art.
[0009] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned cast aluminum-copper alloy.
[0010] The technical solution adopted by the present invention to solve the first technical problem mentioned above is: a cast aluminum-copper alloy, characterized in that, by weight percentage, the cast aluminum-copper alloy is composed of the following components: 4.5 wt.% < Cu < 4.9 wt.%, 0.45 wt.% < Mg < 0.6 wt.%, 0.9 wt.% < Mn < 1.12 wt.%, 0 < Ce < 1 wt.%, with the balance being Al.
[0011] Specifically, the Cu, Mg, Mn, and Ce satisfy the following conditions: 4.53 wt.% ≤ Cu ≤ 4.82 wt.%, 0.48 wt.% ≤ Mg ≤ 0.58 wt.%, 1 wt.% ≤ Mn ≤ 1.11 wt.%, and 0 < Ce ≤ 0.51 wt.%.
[0012] The technical solution adopted by the present invention to solve the second technical problem mentioned above is: a method for preparing a cast aluminum-copper alloy, wherein the cast aluminum-copper alloy is the aforementioned aluminum-copper alloy, and the preparation method includes the following steps in sequence:
[0013] 1) Prepare raw materials according to the above alloy composition. Cu, Mn and Ce elements in the alloy are added in the form of Al-Cu, Al-Mn and Al-Ce master alloys respectively. Al and Mg are added in the form of pure metal. The burn-off of pure Mg and Al-Ce master alloy is 5-10%. Preheat the prepared raw materials to remove the moisture in the alloy raw materials. At the same time, wrap the Al-Ce alloy with aluminum foil.
[0014] 2) Coat the molds, slag skimmers and bell jars required for alloy casting with boron nitride coating, and heat and dry them. The molds used for alloy fluidity testing need to be preheated after coating.
[0015] 3) Heat pure Al and Al-Cu master alloy to complete melting, let stand and cool to 740-760℃, then introduce argon gas with a purity ≥99.9% to refine the melt and remove slag with a slag skimmer. After removing the slag, press the Al-Ce master alloy into the melt with a bell jar and stir. Let stand for 10-20 minutes to form a casting.
[0016] 4) Perform solution treatment and under-aging heat treatment on the castings. Solution treatment: hold at 520-525℃ for 8-12 hours and then water cool; under-aging heat treatment: hold at 165-175℃ for 8-12 hours and then air cool.
[0017] In the above preparation method, adding the Al-Ce master alloy to the aluminum-copper alloy melt can refine the primary grains and effectively reduce the secondary dendrite spacing of the alloy, purify the melt, and form a second phase containing rare earth elements, thereby simultaneously improving the flow properties and mechanical properties of the cast aluminum-copper alloy.
[0018] Preferably, in step 4), the solution treatment is held at 525°C for 12 hours, and the under-aging heat treatment is held at 175°C for 12 hours.
[0019] Specifically, in step 1), the preheating temperature is 100-140℃ and the preheating time is 1-2 hours.
[0020] Specifically, in step 2), the melting tools are dried at 150-200°C for 1-2 hours, and the molds used for alloy fluidity testing are preheated at 200-300°C for 2-4 hours.
[0021] Preferably, in step 1), the Al-Cu, Al-Mn, and Al-Ce master alloys are Al-50%Cu, Al-10%Mn, and Al-30%Ce, respectively.
[0022] Compared with existing technologies, the advantages of this invention are as follows: The aluminum-copper cast aluminum alloy contains only Cu, Mg, Mn, Ce, and Al, with no other elements, ensuring a simple composition. Specifically, the addition of less than 1 wt.% rare earth Ce significantly refines the grain structure, narrowing the dendrite spacing. Simultaneously, the addition of Ce transforms the continuous network morphology of the Al2Cu and Al6Mn second phases at grain boundaries into a discontinuous framework, reducing the cutting effect of the second phases on the matrix and improving the room-temperature mechanical properties of the alloy. Furthermore, the addition of Ce generates a high-temperature resistant hard rare earth compound, Al8Cu4Ce, which has a "pinning" effect on grain boundaries, effectively hindering grain boundary slip at high temperatures and improving the high-temperature mechanical properties of the alloy. Additionally, by adding rare earth Ce, this invention absorbs hydrogen in the melt, reducing oxide inclusions and thus purifying the melt, thereby increasing the alloy's fluidity. Furthermore, the addition of Ce lowers the solidus temperature and Al2Cu eutectic temperature of the alloy, prolongs the melt flow time, delays dendritic coherence, increases the time for mass feed of the melt, and improves the melt fluidity of the Al-Cu alloy, thereby enhancing the alloy's filling capacity. The aforementioned cast aluminum-copper alloy meets the manufacturing requirements for automotive engine cylinder block parts and satisfies the needs of large-scale production. Attached Figure Description
[0023] Figure 1 The as-cast metallographic structures of the alloys with different Ce contents are shown, where (a) 0 Ce; (b) 0.1 Ce; (c) 0.2 Ce; (d) 0.3 Ce; (e) 0.4 Ce; and (f) 0.5 Ce.
[0024] Figure 2 The image shows a comparative example of the microstructure of an as-cast aluminum-copper alloy.
[0025] Figure 3 Scanning electron microscope image of the as-cast microstructure of an aluminum-copper alloy with 0.4 wt.% Ce added;
[0026] Figure 4 XRD patterns of as-cast alloys with different Ce contents;
[0027] Figure 5 Photographs of spiral specimens of aluminum-copper alloys with different Ce content additions;
[0028] Figure 6 DSC curves of aluminum-copper alloys with different Ce content additions. Detailed Implementation
[0029] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0030] Example 1:
[0031] The composition of the cast aluminum-copper alloy in this embodiment, by weight percentage, is: Cu 4.53wt.%, Mg 0.58wt.%, Mn 1.06wt.%, Ce 0.06wt.%, with the balance being Al.
[0032] The method for preparing the cast aluminum-copper alloy in this embodiment includes the following steps:
[0033] 1) Prepare raw materials according to the above alloy composition. Cu, Mn, and Ce elements in the alloy are added in the form of Al-Cu, Al-Mn, and Al-Ce master alloys, respectively. Al and Mg are added in the form of pure metals. The burn-off of pure Mg and Al-Ce master alloys is 5-10%. Preheat the prepared raw materials at 100°C for 1 hour to remove moisture from the alloy raw materials. At the same time, wrap the Al-Ce alloy with aluminum foil. The aforementioned Al-Cu, Al-Mn, and Al-Ce master alloys are Al-50%Cu, Al-10%Mn, and Al-30%Ce, respectively. The above-mentioned pure metals refer to those with a purity of not less than 99.9%.
[0034] 2) Coat the molds, slag skimmers and bell jars required for alloy casting with boron nitride coating, and heat and dry them at 150°C for 1 hour. The molds used for alloy fluidity testing need to be preheated at 200°C for 2 hours after coating.
[0035] 3) Heat pure Al and Al-Cu master alloy to complete melting, let stand and cool to 740℃, then introduce argon gas with a purity ≥99.9% to refine the melt and remove slag with a slag remover. After removing the slag, press the Al-Ce master alloy into the melt with a bell jar and stir. Let stand for 10 minutes to form a casting.
[0036] 4) The castings are subjected to solution treatment and under-aging heat treatment. Solution treatment: hold at 525℃ for 12 hours and water cool; under-aging heat treatment: hold at 175℃ for 12 hours and air cool, finally obtaining cast aluminum-copper alloy.
[0037] Example 2:
[0038] The only difference between this embodiment and the above embodiment 1 is that the specific composition is different. Specifically, Cu 4.65 wt.%, Mg 0.56 wt.%, Mn 1.11 wt.%, Ce 0.18 wt.%, and the balance is Al.
[0039] Example 3:
[0040] The only difference between this embodiment and the above embodiment 1 is that the specific composition is different. Specifically, Cu 4.82 wt.%, Mg 0.56 wt.%, Mn 1.08 wt.%, Ce 0.25 wt.%, and the balance is Al.
[0041] Example 4:
[0042] The only difference between this embodiment and the above embodiment 1 is that the specific composition is different. Specifically, Cu 4.67 wt.%, Mg 0.59 wt.%, Mn 1.07 wt.%, Ce 0.43 wt.%, with the balance being Al.
[0043] Example 5:
[0044] The only difference between this embodiment and the above embodiment 1 is that the specific composition is different. Specifically, Cu 4.71 wt.%, Mg 0.55 wt.%, Mn 1.09 wt.%, Ce 0.51 wt.%, and the balance is Al.
[0045] Example 6:
[0046] The only difference between this embodiment and the above embodiment 1 is that the specific parameters in the preparation method are different. Specifically, in step 1), the prepared raw materials are preheated at 120°C for 1.5 hours.
[0047] 2) Coat the molds, slag skimmers and bell jars required for alloy casting with boron nitride coating, and heat and dry them at 180°C for 1.2 hours. The molds used for alloy fluidity testing need to be preheated at 250°C for 4 hours after coating.
[0048] 3) Heat pure Al and Al-Cu master alloy to complete melting, let stand and cool to 750℃, then introduce argon gas with a purity ≥99.9% to refine the melt and remove slag with a slag remover. After removing the slag, press the Al-Ce master alloy into the melt with a bell and stir. Let stand for 15 minutes to form a casting.
[0049] 4) Perform solution treatment and under-aging heat treatment on the castings. Solution treatment: hold at 520℃ for 10 hours and then water cool; under-aging heat treatment: hold at 170℃ for 8 hours and then air cool.
[0050] Example 7:
[0051] The only difference between this embodiment and the above embodiment 1 is that the Mn content is different, Mn is 1 wt.%, and the specific parameters in the preparation method are different. Specifically, in step 1), the prepared raw materials are preheated at 140°C for 2 hours.
[0052] 2) Coat the molds, slag skimmers and bell jars required for alloy casting with boron nitride coating, and heat and dry them at 200°C for 2 hours. The molds used for alloy fluidity testing need to be preheated at 300°C for 3 hours after coating.
[0053] 3) Heat pure Al and Al-Cu master alloy to complete melting, let stand and cool to 760℃, then introduce argon gas with a purity ≥99.9% to refine the melt and remove slag with a slag remover. After removing the slag, press the Al-Ce master alloy into the melt with a bell and stir. Let stand for 20 minutes to form a casting.
[0054] 4) Perform solution treatment and under-aging heat treatment on the castings. Solution treatment: hold at 522℃ for 8 hours and then water-cool; under-aging heat treatment: hold at 165℃ for 10 hours and then air-cool.
[0055] Comparative example:
[0056] The alloy's chemical composition, by weight percentage, is: Cu 4.81 wt.%, Mg 0.48 wt.%, Mn 1.05 wt.%, with the balance being Al. The comparative example does not contain Ce. The smelting, casting, and heat treatment processes for this alloy are the same as in Example 1.
[0057] The melts (i.e., as-cast aluminum-copper alloys) prepared in step 3) of the above embodiments and comparative examples were cast into concentric triple-helix flowability molds for flowability testing. The flowability properties of the alloys were characterized by measuring the helix length of the flowability castings with different alloy compositions. See details [link to relevant documentation]. Figure 5 The data is summarized in Table 1 below; while the mechanical property data is shown in Table 2 below.
[0058] It should be noted that the above-mentioned concentric triple helix flowability mold is specifically described in Chinese invention patent No. ZL202011349280.9, entitled "A Method for Improving the Flowability of Cast Aluminum-Copper Alloys". Figure 1 The sand mold shown.
[0059] Table 1: Test data on the triple helix flow length of Comparative Example 1 and Examples 1-5
[0060]
[0061] As shown in Table 1, the flow properties of the cast aluminum alloys prepared in Examples 1-5 are all superior to those of the cast aluminum alloys prepared in the comparative examples. This indicates that adding an appropriate amount of rare earth element Ce to aluminum-copper cast aluminum alloys can improve the alloy's flow properties, with the flow reaching its maximum when 0.4% Ce is added.
[0062] Table 2: Room temperature mechanical properties of the as-cast alloys in Comparative Example 1 and Examples 1-5
[0063] Comparative Example 1 147 3.6 83 Example 1 146 4.1 93 Example 2 145 4.6 103 Example 3 168 5.1 106 Example 4 192 6.0 119 Example 5 198 4.9 129
[0064] As can be seen from Table 2 above, the mechanical properties of the cast aluminum-copper alloys prepared in Examples 3, 4 and 5 are all better than those of the cast aluminum-copper alloys prepared in the comparative examples. This indicates that adding an appropriate amount of rare earth Ce to aluminum-copper cast aluminum alloys can indeed improve the mechanical properties of the as-cast alloys, such as elongation and hardness.
[0065] The room temperature mechanical properties of the aluminum-copper alloys after heat treatment in step 4) of Examples 4 and 5 and the cast aluminum-copper alloys after heat treatment in step 4) of Comparative Example 1 are shown in Table 3 below; while the high temperature mechanical properties of the cast aluminum-copper alloys after heat treatment in step 4) of Example 4 and the cast aluminum-copper alloys after heat treatment in step 4) of Comparative Example 1 are shown in Table 4 below.
[0066] Table 3: Room temperature mechanical properties of aluminum-copper alloys after heat treatment in Comparative Example 1 and Examples 4 and 5
[0067] Comparative Example 1 239 4.0 104 Example 4 269 6.8 137 Example 5 278 5.0 136
[0068] As can be seen from Table 3 above, the room temperature mechanical properties of the aluminum-copper alloys after heat treatment in Examples 4 and 5 are better than those of the aluminum-copper alloy after heat treatment in Comparative Example 1, indicating that adding an appropriate amount of rare earth Ce to aluminum-copper cast aluminum alloys can improve the room temperature mechanical properties after heat treatment.
[0069] Table 4: High-temperature mechanical properties of alloys from Comparative Example 1 and Example 4 after heat treatment at 300°C
[0070] Comparative Example 1 155 2.3 Example 4 198 3.1
[0071] As shown in Table 4 above, the high-temperature (300℃) mechanical properties of the aluminum-copper alloy in Example 4 after heat treatment are significantly better than those of the aluminum-copper alloy in Comparative Example 1 after heat treatment. Furthermore, the high-temperature mechanical properties of the aluminum-copper alloy in Example 4 are significantly better than those of aluminum-copper alloy ZL206, which also uses rare earth elements as the main strengthening element. The tensile strength of aluminum-copper alloy ZL206 at 300℃ is only 160 MPa. These data demonstrate that the rare earth Ce microalloying method and preparation process involved in this invention can effectively enhance both the flow properties and mechanical properties of aluminum-copper alloys.
[0072] In the above embodiments, the addition of 0.4 wt.% Ce resulted in the greatest improvement in the overall mechanical properties of the alloy. The tensile strength, elongation, and hardness of the as-cast alloy increased by 30.5%, 66.7%, and 43.5%, respectively, while the tensile strength and elongation of the alloy after heat treatment increased by 12.5% and 70.0%, respectively.
[0073] This invention achieves significant grain refinement and narrower dendrite spacing by adding a certain amount of rare earth element Ce to an aluminum-copper based cast aluminum alloy. See details below. Figure 1As shown. The addition of Ce will also change the morphology of the Al2Cu and Al6Mn second phases at the grain boundaries. Figure 2 The continuous network transforms into Figure 3 The discontinuous skeletal structure in the matrix reduces the cutting effect of the second phase relative to the matrix, improving the room-temperature mechanical properties of the alloy. The addition of Ce also generates a high-temperature resistant, hard rare-earth compound, Al8Cu4Ce; see details... Figure 4 As shown, a "pinning" effect is generated at grain boundaries, effectively hindering grain boundary slip at high temperatures and improving the high-temperature mechanical properties of the alloy. This invention, by adding rare earth element Ce, absorbs hydrogen in the melt, reducing oxide inclusions in the melt, thereby purifying the melt and increasing the alloy's fluidity. See details... Figure 5 As shown. Simultaneously, the addition of Ce lowers the alloy's solidus temperature and the Al₂Cu eutectic temperature; see details below. Figure 6 As shown, extending the melt flow time, delaying dendritic coherence, and increasing the time for mass melt feeding improves the melt fluidity of the Al-Cu alloy, thereby enhancing the alloy's filling capacity.
[0074] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A cast aluminum-copper alloy, characterized in that, The cast aluminum-copper alloy is composed of the following components by weight percentage: Cu, Mg, Mn and Ce satisfy: 4.53wt.%≤Cu≤4.82wt.%, 0.48wt.%≤Mg≤0.58wt.%, 1wt.%≤Mn≤1.11wt.%, Ce is 0.43wt.%, and the balance is Al.
2. A method for preparing a cast aluminum-copper alloy, characterized in that, The cast aluminum-copper alloy is the aluminum-copper alloy according to claim 1, and the preparation method includes the following steps in sequence: 1) Prepare raw materials according to the above alloy composition. Cu, Mn and Ce elements in the alloy are added in the form of Al-Cu, Al-Mn and Al-Ce master alloys respectively. Al and Mg are added in the form of pure metal. The burn-off of pure Mg and Al-Ce master alloy is 5-10%. Preheat the prepared raw materials to remove the moisture in the alloy raw materials. At the same time, wrap the Al-Ce alloy with aluminum foil. 2) Coat the molds, slag skimmers and bell jars required for alloy casting with boron nitride coating, and heat and dry them. The molds used for alloy fluidity testing need to be preheated after coating. 3) Heat pure Al and Al-Cu master alloy to complete melting, let it stand and cool to 740-760℃, then introduce argon gas with a purity of ≥99.9% to refine the melt and remove slag with a slag skimmer. After removing the slag, press the Al-Ce master alloy into the melt with a bell jar and stir. Let it stand for 10-20 minutes to form a casting. 4) Perform solution treatment and under-aging heat treatment on the castings. Solution treatment: hold at 520-525℃ for 8-12 hours and then water cool; under-aging heat treatment: hold at 165-175℃ for 8-12 hours and then air cool.
3. The preparation method according to claim 2, characterized in that: In step 4), the solution treatment is held at 525°C for 12 hours, and the under-aging heat treatment is held at 175°C for 12 hours.
4. The preparation method according to claim 2, characterized in that: In step 1), the preheating temperature is 100-140℃ and the preheating time is 1-2h.
5. The preparation method according to claim 2, characterized in that: In step 2), the melting tools are dried at 150-200℃ for 1-2 hours, and the molds used for alloy fluidity testing are preheated at 200-300℃ for 2-4 hours.
6. The preparation method according to claim 2, characterized in that: In step 1), the Al-Cu, Al-Mn, and Al-Ce master alloys are Al-50%Cu, Al-10%Mn, and Al-30%Ce, respectively.
Citation Information
Patent Citations
Preparation method of aluminum-copper alloy material
CN107385296A
Method for improving flowing property of cast aluminum-copper alloy
CN112442612A
Heat treatment process for reducing fatigue crack growth rate of aluminum-copper-magnesium alloy
CN116732455A